Humic acids: The dynamics of mineralization during bioremediation by vermicomposting of soils contaminated by diesel (Research, Society and Development, 2019)
This study had as a primordium to investigate humic acids extracted from soils contaminated by compounds derived from petroleum and that have undergone bioremediation applying vermicomposting. The development of this research aims to answer the following questions: During the bioremediation was the mineralization of the substrate? The humic acids extracted from the soils showed marked differences in the chemical composition after 90 days of the bioremediation process? The justification of the research is that, to date, there have been few studies about the chemical characterization of humic acids extracted from soils that have undergone bioremediation using vermicomposting. In the dynamics of bioremediation of contaminated soils using Eisenia foetida species there is the passage of the active organic matter to its stabilized form, thus producing the humic substances. One way of monitoring the dynamics of degradation is by studying the variation of organic matter, carbon, nitrogen, and others. In order to reach the objectives, several analytical techniques were used to verify the differences in the chemical composition of the humic acids, among them to the ultraviolet/visible absorption spectroscopy and the spectroscopy in the IV. At the end, the main results show qualitative and quantitative changes in the composition of humic acids. The results show a decrease in the C / N ratio. The functional groups were the most sensitive to the changes caused by the process, evidenced by the increase in total acidity. By the infrared spectra it was possible to visualize a clear decrease in the intensity of the bands in the region 3923-2850 cm-1, corresponding to the aliphatic stretches, evidencing the dynamics of humification during bioremediation.